Aplikasi batik Bangkalan Madura dan anyaman kulit dalam perancangan sepatu wanita - R.A. Sekartaji Suminto (Institut Seni Indonesia Yogyakarta, 2019)
This study tries to make a unique alternative to women's shoes using Bangkalan batik material, Madura, which is decorated or accented with woven cow leather. The hope is to encourage innovation that makes additional products for shoe craftsmen in the Yogyakarta region. The initial target to be achieved in this study is collecting data on shoes, specifically women's shoes, Bangkalan batik motifs, Madura, and data on tanned leather, as well as types of webbing. The method used in this research and publication is literature study, observation, exploration, experimentation, and embodiment. The expected benefit of this research is to support the creative industries that are now being promoted by the government, specifically to provide innovative alternatives to shoe products, in this case women's shoes with various alternative ingredients. In addition, the main objective of this research is to socialize Bangkalan batik, Madura for the people of Yogyakarta, and the general public in general.Key words: women's shoes, Bangkalan Madura batik, cow leather